Islamic Financial Literacy, Promotion, and Brand Image Toward Saving Intention in Sharia Bank - Achmad Zainul Rozikin (Iqtishadia, 2020)
This paper aims to empirically examine the relationship between Islamic financial literacy, promotion, brand image with the intention of saving in Islamic banks. The data in the study were taken from 125 respondents. Respondents in this study were customers of Islamic banks, conventional banks, and were not yet customers of the two banks. This study uses quantitative research methods, which to analyze using multiple regression models and assisted with SPSS 21 application. The results of this study indicate that Islamic financial literacy, promotion, and brand image affect the intention to save in Islamic banks.